2016
DOI: 10.1097/ta.0000000000000925
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, controlled clinical evaluation of surgical stabilization of severe rib fractures

Abstract: Therapeutic study, level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
147
2
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(162 citation statements)
references
References 11 publications
3
147
2
10
Order By: Relevance
“…Three randomized clinical trials, as well as other cohort studies, demonstrate a reduced need for mechanical ventilation, less pneumonia, less pain, and reduced ICU stay in this population when early surgical intervention was performed (8)(9)(10)(11)(12)(13)(14). Three recent meta-analyses confirm these findings, and suggest a mortality benefit as well (15)(16)(17).…”
Section: Indications For Surgerysupporting
confidence: 68%
See 1 more Smart Citation
“…Three randomized clinical trials, as well as other cohort studies, demonstrate a reduced need for mechanical ventilation, less pneumonia, less pain, and reduced ICU stay in this population when early surgical intervention was performed (8)(9)(10)(11)(12)(13)(14). Three recent meta-analyses confirm these findings, and suggest a mortality benefit as well (15)(16)(17).…”
Section: Indications For Surgerysupporting
confidence: 68%
“…Two recent cohort studies (12,23) have demonstrated a benefit in these selected patients, although further study dedicated to this question is needed. Clearly, though, several of the indications described for surgical intervention may be present in non-flail segment patients.…”
Section: Indications For Surgerymentioning
confidence: 99%
“…Standardized approaches are still lacking and the importance of defining clinical indications and incorporating surgical rib fixation into practice has sparked the development of practice guidelines and algorithms to encourage a standardized approach to be taken for patients with chest injury. Some common themes and indications for rib fixation include; 3 or more rib fractures with displacement of more than 1 rib cortical diameter, flail segment, worsening pulmonary status, mechanical ventilation, uncontrolled pain, lung impalement and pulmonary herniation [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…SSRF has been shown to be most effective in decreasing pain and liberating patients from mechanical ventilation [3]. Prolonged mechanical ventilation is associated with recurrent pneumonia and possibly death.…”
Section: Commentmentioning
confidence: 99%
“…(Ann Thorac Surg 2018;106:e121-3) Ó 2018 by The Society of Thoracic Surgeons S urgical stabilization of rib fractures (SSRF) in patients with flail chest has been shown to decrease length of stay, pain, need for mechanical ventilation, and mortality [1][2][3][4]. The risk of hardware infection after SSRF is between 0% and 10% in all patients [5].…”
mentioning
confidence: 99%